Hydroponic forage in the Cerrado Pantanal ecotonon (Research, Society and Development, 2021)
Hydroponic fodder is a short-term production technology, continuous production, cultivation in all seasons, high productivity, low water consumption. Seeking to reverse the climatic adversities suffered by producers to feed their animals, the objective of this work was to evaluate the productivity and the quality of hydroponic forage in the Cerrado-Pantanal ecotone, seeking to determine the species and the most appropriate solution for the region. Two experiments were carried out at the State University of Mato Grosso do Sul, in the municipality of Aquidauana - MS, in a greenhouse with a 50% shading screen. The first experiment was implemented in March and the second in September, both being conducted for 15 days. The experimental design was in randomized blocks, in subdivided plots. The plot was formed by the solutions (mineral and organic) and the subplots were the populations (100% corn, 100% corn + 8 mucuna seeds, 100% millet, 50% corn + 50% millet, 75% corn + 25% millet and 25% corn + 75% millet) with four replications totaling 12 treatments. The plots contained 1 m2 and received 4 liters of their respective solution for 11 days. The population constituted of 25% corn and 75% millet irrigated with mineral solution showed better quality of forage in terms of crude protein. The population of maize and maize + mucuna obtained the highest dry matter regardless of the solution.